Send the boy to sea : the memoirs of a sailor on the goldfields - Smith, James Montagu; Cuffley, Peter (Noble Park, Vic. : Five Mile Press, 2001)
The factual account of the life of a troublesome boy, sent to sea at the age of 14 in 1851, and his experiences while sailing on convict ships between England and Australia. Also his love of Australia which led him to the Victorian goldfields, and finally to Maitland NSW where he settled.
Includes index.
Bibliography: p. 309-312.
Keywords: Smith, James Montagu; Sailors -- England -- Biography; Gold miners -- Australia -- Biography; Immigrants -- Australia -- Biography; Gold mines and mining -- Australia -- History